(Des) construindo narrativas em A caverna, de José Saramago - Alves, Maria Aparecida Rodrigues (2015)
This study proposes to investigate the metafictional strategies present in the novel A Caverna, by José Saramago, as well as to demonstrate how the author, using intertextuality, proposes sometimes either the (re)formulation or the (re) affirmation of other people's speeches, building and baring a text that remains on the threshold. To carry out this purpose, the research is organized into three chapters. In the first, entitled "Contemporary Tendencies in Portuguese Literature", we present a brief overview of contemporary Portuguese romance and its main tendencies, as well as the literary journey undertaken by Saramago. Considerations of Miguel Real and Alvaro Cardoso Gomes in the reconstruction of this Portuguese literary scene, and interviews and critical comments about his own work, made by Saramago, were essential in this chapter. In "Discourses on the threshold: between (re)affirmation and the (re)formulation," the second chapter of the study, we discuss the concept of metafiction proposed by Linda Hutcheon and commented by Gustavo Bernardo and present the metafictional strategies employed by the author in the construction of the studied novel and the effects of meaning generated by such employment. The intertextuality the resumption of popular sayings, the Bible discourse or the dialog with other unrelated texts the intratextuality and metalanguage were evidenced here. In the last chapter, "Dialogues between Saramago and Platonic caves", it s investigated the intertextual dialogue established between the novel of Saramago and the myth of Plato's cave, suggested from the very title of the work. The objective was to thus display as through the resumption of foreign texts, the Portuguese author moves between the (des)construction and (re)construction of the speeches, creating a threshold text and requiring the reader his effective participation in the creation of new meanings. The concepts of Kristeva and Jenny, regarding the intertextuality, already employed in chapter two, were quite relevant